Bioresponsive immunomodulator nanocomplex for selective immunoengineering in metastatic lymph nodes - Yueyang Deng; Mo Chen; Tianxu Fang; Tianwen Luo; Xiaona Cao; Guojun Chen (Proceedings of the National Academy of Sciences, 2026)
Lymph node (LN) metastasis (LNM) frequently occurs in various cancer types and is associated with high aggressiveness, poor prognosis, and low survival rates. However, effective clinical interventions remain limited primarily due to the distinctive immunosuppressive microenvironment found in metastatic LNs. Targeted delivery of immunomodulators and selective immunoengineering in metastatic LNs offers a promising avenue for repurposing these LNs as an effective antitumor system while mitigating the risk of unwanted immune activation elsewhere. Here, we develop a bioresponsive LN-targeted immunomodulator nanocomplex designed to selectively reprogram the immune microenvironment in metastatic LNs for LNM inhibition. The immunomodulator nanocomplex can target LNs due to specific chemokine receptor 7 modification and selectively release anti-PD-1 antibodies in response to glutathione that is found elevated in the extracellular matrix of metastatic LNs. In two mouse models, our data suggested that the immunomodulator nanocomplex can selectively activate T cell–mediated antitumor immune responses in metastatic LNs and thus effectively inhibit tumor growth and prolong the survival of animals. Importantly, the modular design of this platform could enable facile incorporation of alternative immunotherapeutic agents that exhibit significant systemic toxicities in the clinic, allowing broader application to payloads that may particularly benefit from localized, LNM-selective activation. This approach holds significant promises for reducing the necessity for complete LN dissection, thereby presenting a valuable therapeutic option for a broad spectrum of cancer patients.